PEMBUATAN ASAM GLUKONAT DARI GLUKOSA DENGAN PROSES FERMENTASI MENGGUNAKAN Aspergillus niger - Latifah, Ir; HP, Sudaryati; E, Hariyono (REKAPANGAN, 2010)
Gluconic  acid  is  a  product  of  the  dehydrogenation  of  glucose,  and  used  widely  industry. Gluconic acid which is crystallized in the form-δ-lactone glukono can be used to substitute for yeast in bread making and other food industries. The more 50,000 tons of gluconic acid were produced by fermentation using Aspergilus niger of material containing glucose. The  purpose  of  this  study  to  determine  the  best  treatment  volume  and  the  fermentation  time starter in the production of gluconic acid from glucose by fermentation with Aspergillus niger. This research used Completely Randomized Design (CRD) with factorial pattern consisting of 2 factors with 2 repetitions. The first factor  is the length of fermentation (12 and 18, and 24 hours)  and  the  second  factor    is  the  volume  of  starter  (12,  16;  and  20  mL)  .  The results showed that the best treatment there is the treatment of fermentation time 24 hours and the volume of 16 ml starter, which produces gluconic acid with a concentration = 7.405%, density = 1.1559 g / ml, pH = 3.4, biomass = 8.5580 gr .